Effect of Problem-Based Learning Assisted by Wordwall on Science Learning in Elementary Schools - Gilang Kurniawan; Darwati Darwati; Fadly AS; Puja Prima Andesda (International Journal of Multidisciplinary Research of Higher Education, 2026)
Science learning in elementary schools plays a crucial role in fostering students’ critical thinking skills. This study investigates the effect of implementing the Problem-Based Learning (PBL) model assisted by Wordwall in science education at an elementary school. A quasi-experimental design with a one-group pretest–posttest approach was employed, involving 14 students (N = 14). Research instruments included a validated and reliable multiple-choice achievement test, observation sheets of learning activities, and student response questionnaires. Data were analyzed using normality tests, N-gain, and paired t-tests with SPSS 21. The findings revealed a significant improvement in student learning outcomes, with mastery increasing from 35.71% (5 students) to 92.85% (13 students). The paired t-test produced a t-value of 9.165 with a significance level of p = 0.00006 (< 0.05), indicating a highly significant difference before and after the intervention. These results suggest that the Problem-Based Learning model assisted by Wordwall is effective in enhancing science learning achievement and holds potential for application across other subjects and learning contexts.